Understanding invisible pain in the older adult: a content analysis of social media’s representation of herpes zoster vaccine - Yang, Mingyi; Yang, Yiran; Li, Shuyue (Frontiers in Public Health, 2024)
Herpes zoster (HZ), as a common disease in older adults, affects their quality of life. Therefore, this study aims to examine the presentation of HZ-related information on social media platforms to analyze residents' attitudes and behaviors towards the dissemination of health information. This research used content analysis to focus on Weibo, a representative social media in mainland China, to analyze the content of 1866 blog posts related to herpes zoster (HZ) and herpes zoster vaccine (HZV). According to the consistency test by Cohen's Kappa, four themes were identified: (a) source, (b) tones, (c) epidemiological information, and (d) EPPM elements. The findings showed that most information on Weibo came from non-professionals, with a neutral tone, and showed the invisible pain of HZ and the effectiveness of HZV through the two largest aspects prevention and aged protection in epidemiological information. However, current blog posts treat the elderly as invisible individual, failing to acknowledge them as recipients of information. Additionally, the cost of the vaccine acts as an invisible economic barrier, contributing to the dissemination of incorrect information about folk remedies. This, it impacts the elderly's acceptance of health information related to HZV. Thus, the way to share health information with the elderly needs to be improved in the future, and attention should be paid to the transmission of incorrect information to improve their vaccination rates and awareness of health management.